The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0234656
|View full text |Cite
|
Sign up to set email alerts
|

Summer, sun and sepsis—The influence of outside temperature on nosocomial bloodstream infections: A cohort study and review of the literature

Abstract: Background The incidence of many infections is seasonal e.g. surgical site infections, urinary tract infection and bloodstream infections. We questioned whether there is seasonal variation even in climate-controlled hospitalized patients, and analyzed the influence of climate parameters on nosocomial bloodstream infections. Methods and findings The retrospective cohort study is based on two databases: The German national surveillance system for nosocomial infections in intensive care units (ICU-KISS) from 2001… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…Authors reported a significant increase in the likelihood of hospitalacquired bloodstream infections caused by gram-negative bacteria (particularly Acinetobacter spp and Enterobacter spp) in months with higher mean temperatures. 30 The similarity of our results to the findings of Schwab et al indicates that meteorological factors impact the occurrence and causing pathogens of not only SSIs but also other healthcare-associated infections. Overall, explanations for the observed results and shifts in pathogen distribution attributable to temperature remain speculative to a certain extent due to the novelty of this type of research and the lack of data on interactions of the human microbiome and infection vulnerability.…”
Section: Discussionsupporting
confidence: 89%
“…Authors reported a significant increase in the likelihood of hospitalacquired bloodstream infections caused by gram-negative bacteria (particularly Acinetobacter spp and Enterobacter spp) in months with higher mean temperatures. 30 The similarity of our results to the findings of Schwab et al indicates that meteorological factors impact the occurrence and causing pathogens of not only SSIs but also other healthcare-associated infections. Overall, explanations for the observed results and shifts in pathogen distribution attributable to temperature remain speculative to a certain extent due to the novelty of this type of research and the lack of data on interactions of the human microbiome and infection vulnerability.…”
Section: Discussionsupporting
confidence: 89%
“…Air temperature and relative humidity have been reported to correlate with indoor microbial community richness in different buildings and environments [ 1 , 16 , 63 , 64 ]. Moreover, in the clinical setting, a number of studies have already reported seasonal and temperature-associated increases of bacterial bloodstream infections [ 65 , 66 ] and surgical site infections [ 67 ] in hospitalized patients. In our study, air temperature and relative humidity were recorded in all rooms at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the rate of patients with IDU-IE were lower during the winter compared to the other seasons, which according to our knowledge, has not been presented before. Seasonal changes in infectious diseases have been described before [ 20 ]. Most bacteria tend to increase with rising temperature [ 20 ], which could possibly explain the lower rate of IE during the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in infectious diseases have been described before [ 20 ]. Most bacteria tend to increase with rising temperature [ 20 ], which could possibly explain the lower rate of IE during the winter season. The decrease in incidence of IDU-IE after 2011 might be explained by a syringe exchange programme that was introduced in Stockholm at that time.…”
Section: Discussionmentioning
confidence: 99%